PENGARUH PENDIDIKAN KESEHATAN TERHADAP PERILAKU HIGIENE VULVA PADA REMAJA PUTRI DI PONDOK PESANTREN Al-FITHRAH SURABAYA - Hasfinda Fakhir Mufid, NIM011511223001 (2017)
Vulvar hygiene behavior is knowledge, attitude, and practice or action to care for external genital organ which aims to maintain cleanliness, health, and prevent infection. Based on preliminary studies and previous studies, adolescent vulvar hygiene behavior is lacking. Person's health behavior can be changed by providing health education. This study aims to analyze the effect of health education on vulvar hygiene behavior in adolescent. This research method is pre-experimental designs with one group pretestposttest design. The number of samples is 90 high school students with sampling technique using proportional random sampling. The independent variable is health education given in 4 meetings by lecture method, demonstration, and group discussion (one meeting per week). The dependent variable is the vulvar hygiene behavior which consists of 3 sub variables namely knowledge, attitude, and practice. The measuring tool used in this research is the questionnaire and data analysis using Wilcoxon signed rank test. The results showed that the category of good knowledge increased from 8.9% to 74.4% and none were in the less category. The category of excellent attitude increased from 10% to 77.8% and none were in the less category. Good practice increased from 2.2% to 31.1% and the less category became reduced. Result of Wilcoxon signed rank test pretest-posttest data knowledge p = 0,000 (p <0,05), attitude p = 0,000 (p <0,05), and practice p = 0,000 (p <0,05). Those results indicate that there is an influence of health education on vulvar hygiene behavior in adolescent.